Case report: Novel compound heterozygosity for pathogenic variants in MED23 in a syndromic patient with postnatal microcephaly - Salzano, Emanuela; Niceta, Marcello; Pizzi, Simone; Radio, Francesca Clementina; Busè, Martina; Mercadante, Francesca; Barresi, Sabina; Ferrara, Arturo; Mancini, Cecilia; Tartaglia, Marco; Piccione, Maria (Frontiers in Neurology, 2023)
Biallelic loss-of-function variants in MED23 cause a recessive syndromic intellectual disability condition with or without epilepsy (MRT18). Due to the small number of reported individuals, the clinical phenotype of the disorder has not been fully delineated yet, and the spectrum and frequency of neurologic features have not been fully characterized. Here, we report a 5-year-old girl with compound heterozygous for two additional MED23 variants. Besides global developmental delay, axial hypotonia and peripheral increased muscular tone, absent speech, and generalized tonic seizures, which fit well MRT18, the occurrence of postnatal progressive microcephaly has been here documented. A retrospective assessment of the previously reported clinical data for these subjects confirms the occurrence of postnatal progressive microcephaly as a previously unappreciated feature of the phenotype of MED23-related disorder.